An examination of the role of the Public Library in Cape Town, in support of Early Childhood Development, with special reference to Harare Public Library, Khayelitsha - Fako, Sipho (Library and Information Studies Centre (LISC), 2019)
The purpose of this study was to investigate the role of the Harare Public Library, Khayelitsha, in empowering Early Childhood Development Centres (crèches and nursery schools) in its community. The researcher focused on the relationships the library has with Early Childhood Development Centres in its community, and the non-profit organisation (NPO) providing educational services. It is argued that the provision of ECD will help reduce the cycle of poverty by strengthening the educational foundation of South Africa’s children. The main finding of the study is that strong relationships between libraries and other community stakeholders are critical in offering a better future for the children of disadvantaged communities.